Bistability-induced chimeras in one-dimensional paced excitable rings with nonlocal couplings. (20th September 2022) - Lei, Zhao; Pu, Shujie; Zhang, Hao; Yao, Chenggui; Qian, Yu; Zheng, Zhigang
Abstract: In this paper, we provide a bistability mechanism for giving rise to a new kind of chimeras in the one-dimensional (1D) paced nonlocally coupled excitable rings without rotational coupling scheme. It is shown that the elements in the system can perform distinct modes and give rise to the chimera pattern. By analyzing the response dynamics in the corresponding local excitable model with the same pacing, the initial-excitation–dependent bistability feature is revealed as the mechanism responsible for this chimera state. Furthermore, this bistability-induced chimera state is found to be pacing dependent, and the chimera parameter regions on the phase plane of pacing amplitude and frequency are shown explicitly. Importantly, this new kind of chimera pattern can also self-organize to emerge in other paradigmatic network models, implying the genericity of the bistability mechanism in inducing chimeras in paced excitable complex networks. The present work is expected to shed light on new perspectives of the chimeras in excitable systems.